Effect of pretreatments on the quality of the cabinet-dried white button mushroom (Agaricus bisporus) - Arumuganathan, T; Kamal, Shwet; Rai, R D; Kumar, Rajesh; Tewari, R P (Mushroom Research, 2017)
Investigations were conducted to extend the shelf-life of the button mushroom and standardize a simple and low-cost dehydration technology as an alternate to the high-cost and energy-intensive preservation. Three treatments viz. blanching, steeping with KMS + Citric acid + EDTA and steeping with blanching were taken as pretreatments. It was observed that blanching treatment had lowest rehydration ratio and low in final yield also with unattractive appearance with poor reconstitution quality. Whereas un-blanched mushroom gave highest browning index during drying and storage, more intense after re-hydration making product most unacceptable. Although control showed good results immediately after drying but fast discolouration during storage was observed. Steeping of unblanched mushrooms for 12 hours gave higher yield and lower rehydration ratio of the dehydrated product than blanched and steeped treatment, resulted in the lowest browning and highest rehydration ratio. The mean organoleptic score established its superiority over other treatments with regard to quality attributes. Non-enzymatic browning showed an upward trend, while the rehydration ratio and mean organoleptic scores declined with the storage period.Â